Historical Studies of Christian Education and Its Implementation in the Industrial Revolution 4.0 - Kasiatin Widianto (Jurnal Didaskalia, 2021)
The term ‘double predestination’ simply means that, just as God predestines some, but Education is something that is very important for human life, and this is a divine mandate. This study aims to determine the pattern of Christian education from time to time and its implementation in the Industrial Revolution 4.0 era. This study uses a qualitative method with a literature study approach by reading, observing and analyzing literature sources on Christian education from time to time and its implementation in the Industrial Revolution Era 4.0. The results show that the situations and conditions behind the presence of education differ from time to time, but the similarity is that God has appointed certain people as agents of education. Where the patterns that are applied are harmonized with the surrounding conditions.